'Unity in Diversity': Non‐sectarian Social Movement Challenges to the Politics of Ethnic Antagonism in Violently Divided Cities. (5th July 2012) - NAGLE, JOHN
<x xml:space="preserve">Abstract</x> Abstract Divided cities are defined by a violent conflict of ethnonationalism and characterized by semi‐permanent ethnic cleavages, high levels of endogamy and social segregation. Yet the perception that divided cities are wholly framed by the politics of ethnic homogeneity is challenged by a number of its citizens who refuse to be interminably circumscribed by ethnic politics. These 'actors' mobilize in social movements that promote non‐sectarian politics and identities. They also include the protests of environmentalists, trade unionists and the celebrations of gay groupings. This article critically explores how such urban social movements may help ameliorate or contest the politics of ethnic antagonism in divided cities. It explores this issue in the context of debates regarding peacebuilding projects in divided cities, especially those that promote accommodative solutions to ethnic conflict, and shows how social movement mobilization may augment political power sharing. Focusing on non‐sectarian social movement mobilization in Belfast, Northern Ireland, the article critically analyses movements in three ways: creating intercommunal networks; fostering a public sphere of debate; and challenging the programmed uses of segregated space. Résumé Définies par un conflit violent de nature ethnonationaliste, les villes divisées se caractérisent par des clivages ethniques semi‐permanents, ainsi que par des niveaux élevés d'endogamie et de ségrégation sociale. L'idée que ces villes sont entièrement régies selon des critères d'homogénéité ethnique est pourtant remise en cause par certains habitants qui refusent d'être contraints indéfiniment par une politique ethnique. Ces 'acteurs' se mobilisent dans des mouvements sociaux aux buts politiques ou identitaires non sectaires, qui englobent aussi des manifestations écologistes ou syndicalistes et des regroupements homosexuels. Une analyse critique étudie comment ces mouvements sociaux urbains peuvent améliorer ou contester la politique d'antagonisme ethnique des villes divisées. Pour ce faire, elle se place dans le cadre des débats sur les actions de consolidation de la paix dans ces villes, en particulier s'ils encouragent la résolution des conflits par la conciliation; elle montre en outre comment la mobilisation de mouvements sociaux peut accentuer le partage du pouvoir politique. La mobilisation de mouvements sociaux non sectaires à Belfast, en Irlande du Nord, est examinée plus particulièrement et sous trois angles: créer des réseaux intercommunautaires, favoriser une sphère de débat publique et s'opposer aux usages programmés des espaces ségrégués.